2015
DOI: 10.1016/j.nicl.2015.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Default mode network segregation and social deficits in autism spectrum disorder: Evidence from non-medicated children

Abstract: Functional pathology of the default mode network is posited to be central to social-cognitive impairment in autism spectrum disorders (ASD). Altered functional connectivity of the default mode network's midline core may be a potential endophenotype for social deficits in ASD. Generalizability from prior studies is limited by inclusion of medicated participants and by methods favoring restricted examination of network function. This study measured resting-state functional connectivity in 22 8–13 year-old non-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
109
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(132 citation statements)
references
References 86 publications
23
109
0
Order By: Relevance
“…For example by involving EXE and DMN, that are usually functionally anticorrelated, an insightful metric to test our classifier could be developed. In the study of Yerys et al (2015) [33] , the ASD groups demonstrated under-connectivity within the DMN, and a poorer network segregation of its midline core functional connectivity, as compared with controls. This midline core of the DMN encompassed the medial prefrontal cortex and posterior cingulate cortex.…”
Section: Discussionmentioning
confidence: 95%
“…For example by involving EXE and DMN, that are usually functionally anticorrelated, an insightful metric to test our classifier could be developed. In the study of Yerys et al (2015) [33] , the ASD groups demonstrated under-connectivity within the DMN, and a poorer network segregation of its midline core functional connectivity, as compared with controls. This midline core of the DMN encompassed the medial prefrontal cortex and posterior cingulate cortex.…”
Section: Discussionmentioning
confidence: 95%
“…Although previous research has associated ASD phenotypes with widespread hypoconnectivity 131,132,207,208,211,212 , we hypothesized that "noisy brains" were a more plausible explanation-rather than being disconnected, individuals expressing autistic-like traits would exhibit transient, dynamic connectivity that might otherwise deflate "static" estimates over the course of a scan. We proposed increased OXTR methylation as an underlying mechanism, such that decreased access to endogenous oxytocin would produce less-robust functional connections.…”
Section: Discussionmentioning
confidence: 96%
“…The dDMN largely corresponds to what others have termed the dorsal medial subsystem-these regions, primarily spanning the posterior cingulate and medial PFC, are frequently associated with empathetic processes such as mentalizing and perspective-taking 205,206 . Accordingly, connectivity across these regions is compromised in ASD 207,208 . The vDMN is relatively intact, by contrast-it comprises a medial temporal subsystem that is primarily associated with mental time-travel and other autobiographical memory-related functions 205,206 .…”
Section: Network Selection and Timeseries Extractionmentioning
confidence: 99%
See 2 more Smart Citations